PHONON DYNAMICS IN NEUTRON STAR CRUSTS AND THEIR CONNECTION TO PULSAR GLITCHES - Nasirova, D.M.; Kurmangaliyeva, V.O.; Gazizova, А.А.; Takibayev, N.Zh.; Odsuren, M. (Eurasian Physical Technical Journal, 2026)
This paper investigates the role of phonon dynamics in the solid crust of neutron stars and their connection to large-scale structural instabilities. Electron capture reactions in the dense outer layers of compact stars generate excited nuclei, which may transfer their energy to the lattice in the form of phonons. These vibrational modes affect the elastic response of the crust, modifying its stress–strain behavior under extreme astrophysical conditions. Using fundamental parameters such as Young’s modulus, density, and sound velocity, we estimate phonon frequencies, wave numbers, and lifetimes across different crustal layers. Numerical analysis indicates that phonon excitations are capable of storing elastic energy and may act as precursors of sudden stress release events. A special focus is given to pulsar glitches, with the Vela pulsar serving as a representative example. The comparison between calculated phonon energies and observed glitch energetics suggests that collective phonon processes could contribute to the mechanism of these abrupt rotational irregularities. By emphasizing the importance of lattice dynamics in neutron star models, this work provides the first quantitative estimates linking microscopic phonon excitations with macroscopic glitch energetics, thus contributing to a deeper understanding of how nuclear-scale transitions manifest as observable astrophysical signals. These findings can contribute to future models of neutron star crust dynamics and related astrophysical observations.